Austempered ductile iron for gears - Guesser W.L.* (2012)
It is discussed the use of ADI (Austempered Ductile Iron) for gears. The gears were produced from continuous cast iron bars, heat treated for grade 3 of ASTM ADI Standard A897M-06 (UTS >1200 MPa), and compared to carburized steel AISI 8620 and to induction hardened steel AISI 4140. Tests on gears were made using equipment developed at UTFPR, measuring the time for pitting and spalling on the surface of the gears. The results show very good potential of using ADI for gears, replacing induction hardened steels. The results show too that the nodule size affects the life of gears, independently of the mechanical properties of the matrix. The ADI with smallest nodules show higher life for pitting formation. It is discussed additionally the mechanisms of crack propagation under the surface of the gears, for all tested materials. Copyright © 2012 SAE International.